The effect of leadership styles on service quality and price satisfaction and the moderating role of organizational culture in oil and gas industry - Bakheet, Almuharrami Suhail Saeed Mohamed (2022)
The oil and gas industry in the United Arab Emirates (UAE) has witnessed vital transformations over the last decade which restructuring the oil and gas industry leadership for re-assessing the optimal leadership style and its impact on the provided services quality and price satisfaction. The UAE government has determined to reform the country's oil and gas sector, and one of the primary considerations was to choose new leadership. The new leadership has established a new strategy, with the primary objective of lowering the cost of gas and oil production while preserving the quality of delivered services. Thus, the purpose of this study is to investigate three main leadership styles that contributed to the service quality and price satisfaction with the moderating role of organizational culture among the oil and gas industry in the UAE. This study employs a cross-sectional technique; data are collected from the study's intended population via a questionnaire instrument. A total of 768 participants from the industry were targeted by this study. The SPSS program and the SmartPLS program were used in this study for data analysis. The study discovered that Transactional Leadership Style has a positive and substantial impact on pricing satisfaction in the UAE's oil and gas industry, while Transformational and Authentic Leadership Style has a positive and large impact on service quality in the UAE's oil and gas industry. For the moderation effect, the organizational culture significantly moderate on the linkage between leadership styles of transformational, transactional, and authentic and service quality. Based on the findings of the study, it recommends that organizational culture encourages or discourages a process of organizational change, which is why it is important to understand how the learning process works within organizations. Also, the oil and gas industry should differentiate between the transactional leadership style that has the highest impact on price satisfaction and the transformational leadership style that has the highest impact on service quality. It is recommended to boost the transformational leadership style that based on leading by vision as it may possess higher impact on the service quality provided by the oil and gas industry.